2005
DOI: 10.1159/000087188
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Reverses Ethanol-Induced Deficit in Spatial Reference Memory in Castrated Rats

Abstract: The present study was designed to evaluate the effects of ethanol, testosterone and combination of ethanol and testosterone, on spatial reference memory and β-endorphin (β-EN) levels in castrated rats. Male Sprague-Dawley rats (120–150 g) were used in this study, Animals were castrated and ethanol, testosterone or combination of the drugs were administered to rats at 09:00 h. The drugs were administered after a training period of 5 days and spatial reference memory was evaluated for 7 days using the Morris wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 91 publications
5
13
1
Order By: Relevance
“…However, findings that after a week interval GDX rats made significantly more errors and followed longer pathways significantly more than they had previously does suggest some GDX influence on spatial reference memory. This may be in line with findings that T-replacement in GDX rats improves and T administration in gonadally intact rats impairs Morris Water maze spatial reference memory in adult but not aged rats (Goudsmit et al, 1990; Khalil et al, 2005; Spritzer et al, 2011). More recently, GDX-induced and T-attenuated deficits in spatial reference memory evaluated in Y-maze testing under non-rewarded contengencies were found for 48h but not 24h inter-trial intervals (Hawley et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…However, findings that after a week interval GDX rats made significantly more errors and followed longer pathways significantly more than they had previously does suggest some GDX influence on spatial reference memory. This may be in line with findings that T-replacement in GDX rats improves and T administration in gonadally intact rats impairs Morris Water maze spatial reference memory in adult but not aged rats (Goudsmit et al, 1990; Khalil et al, 2005; Spritzer et al, 2011). More recently, GDX-induced and T-attenuated deficits in spatial reference memory evaluated in Y-maze testing under non-rewarded contengencies were found for 48h but not 24h inter-trial intervals (Hawley et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…Results from the current study in which orchidectomy impaired, and testosterone treatment restored, spatial cognition are consistent with a growing body of research conducted over the last decade, which has indicated a beneficial role for testosterone in male rats on a variety of spatial tasks (Daniel et al, 2003;Hawley et al, 2012;Khalil et al, 2005;McConnell et al, 2012;Sandstrom et al, 2006;Spritzer et al, 2011). However, the results of earlier studies that examined the effects of testosterone and other androgens on spatial cognition in male rats were somewhat inconsistent, such that androgen treatment either had no effect (Smith et al, 1996) or impaired performance (Goudsmit et al, 1990).…”
Section: The Effects Of Testosterone On Spatial Cognitionsupporting
confidence: 89%
“…One explanation for this contradiction is that Hawley et al (2012) used an aversively motivated task, suggesting that motivation or stress levels may interact with testosterone level to influence spatial learning and memory. Past studies testing the effects of testosterone on performance in the Morris water maze have shown improvement of (Khalil et al, 2005; Spritzer et al, 2011b), impairment of (Goudsmit et al, 1990; Naghdi et al, 2001), or no effect of testosterone on performance (Hodosy et al, 2010; Isgor and Sengelaub, 1998; Naghdi et al, 2005; Sandstrom et al, 2006; Spritzer et al, 2008). We previously found that a wide range of physiological doses of testosterone, including those used in the current study, did not cause clear differences among treatment groups in their ability to learn reference memory or working memory versions of the Morris water maze (Spritzer et al, 2011b).…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies have shown that castrating male rats impairs their spatial working memory (Daniel et al, 2003; Gibbs and Johnson, 2008; Hasegawa and Mochizuki, 2009; Kritzer et al, 2001; Spritzer et al, 2008), and some studies have shown that testosterone replacement restores spatial working memory (Bimonte-Nelson et al, 2003; Kritzer et al, 2001; Spritzer et al, 2011b). In contrast, most studies to date indicate that testosterone has no effect on spatial reference memory (Hodosy et al, 2010; Naghdi et al, 2005; Sandstrom et al, 2006; Spritzer et al, 2008), but a few have demonstrated testosterone-induced improvements in reference memory (Khalil et al, 2005; Spritzer et al, 2011b). …”
Section: Introductionmentioning
confidence: 96%